Sea Water Distillation Design Using Renewable Energy for Drinking Water - Andi Muhammad Ilyas; Yuliana Yuliana; Muhammad Natsir Rahman; Mochammad Apriyadi Hadi Sirad; Fahrizal Djohar; Md Hasanuzzaman; Zulaeha Mabud (Universitas Khairun, 2024)
The increase in drinking water needs in Ternate City is ttriggered by very rapid population growth. Population growth has resulted in the conversion of forests into housing which has resulted in reduced water catchment areas. In the end, several locations experienced a decline in water quality from fresh to brackish. To overcome the decline in the volume and quality of clean water, a plan is being made to distill sea water into fresh water. The method used in this research is the experimental method. Solar desalination is a process where solar energy is utilized to putify the fresh water from saline/brackish water for drinking purposes, in charging of the batteries, research laboratories. Experimental results with a distillation flow area of 325 cm with an average volume of 43.7 ml. Tests with a distillation drain area of 650 cm produced 76.0 ml of fresh water. Experiments with a distillation flow area of 975 cm produced an average of 106.3 ml of fresh water. The effectiveness of distillation occurs at the widest drainage. The price of fresh water per milliliter is IDR 1.41 cheaper than bottled water, namely IDR. 6.66 per milliliter. The results of research on the salinity of salt water to fresh water show that the salinity of salt water is 35 ppt, while the salinity of distilled water is 0, this shows that the result of distillation is fresh water that can be consumed.